Pengelompokan Jumlah Produksi Pipa dengan Menggunakan Metode Clustering Berdasarkan Ukuran: - Nila Damayanti; Akim M.H. Pardede; Marto Sihombing (VISA: Journal of Vision and Ideas, 2023)
Production is the most basic and important thing in the company. The company will determine how many products to produce, the required capacity, and the raw materials needed to meet demand. PT. Multiplas Prima Jaya is a company engaged in the manufacturing of PVC pipes. So far, the company does not have a well-planned production plan, production is carried out according to the instructions of the owner of the company. In addition, the production schedule can be changed according to the wishes of the owner. As a result, there is a deviation between the number of pipe production and pipe sales that occurs. In addition, the company already knows the series of production planning to the process of executing the plan Keywords: Data Mining,Clustering,PT Multiplas Prima Jaya.